Types and Abundance of Microplastics in Lokan (Geloina erosa) in the Mangrove Ecosystem of Kedabu Rapat Village, Meranti Islands - Putri, Dinda Maharani; Nurrachmi, Irvina; Efriyeldi, Efriyeldi (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
One of the current problems for coastal areas is the high level of plastic waste. This waste degrades into microplastic particles, which can threaten the life of marine biota, including the lokan (G. erosa). Lokan (G. erosa) is used as a bioindicator to study the type and content of microplastics in the mangrove ecosystem. The purpose of this study was to analyze the differences in microplastic abundance between stations and microplastic content between sea turtle sizes, as well as the relationship between shell length and meat weight with microplastic content. This study was conducted from December 2024 to February 2025 in Kedabu Village, Meranti Islands Regency, which directly borders the Malacca Strait. The survey method was used, purposive sampling at three stations: the conservation mangrove area, the mangrove area near the fishing port, and the mangrove area near the settlement. Sea turtles were taken during low tide, each one using a machete. Individual per station. The study results showed that three types of microplastics were found in the lokan (G. erosa): fiber, film, and fragments, with an average of 32.73 particles per individual. There was a significant difference in microplastic content between small and large sea turtles, but microplastic abundance between stations did not differ significantly. The highest microplastic abundance was found at Station 1 (11,331 particles/g). Shell length and meat weight showed a moderate positive relationship with microplastic content